Cri-du-Chat syndrome diagnosed in a 21-year-old woman by means of comparative genomic hybridization (2017)
The cri-du-chat syndrome is caused by a deletion on the short arm of chromosome number 5. The size of genetic material loss varies from the 5p15.2 region only to the whole arm. Prevalence rates range between 1:15000 and 1:50000 live births. Diagnosis is suspected on infants with a high-pitched (cat-like) cry, facial dysmorfism, hypotonia and delayed psychomotor development. In adults, phenotypic findings are less specific. It is confirmed through high-resolution G-banding karyotype, fluorescent in situ hybridization or microarray-based comparative genomic hybridization (a-CGH).The following is the case report of a 21-year-old female patient with severe mental retardation and trichotillomania, who does not control sphincters and does not bathe or eat by herself. Her communication is based only on sounds and dysmorphic facies. The G-band karyotype reported is 46, XX. a-CGH shows 18.583Mb interstitial microdeletion in 5p15.33p14.3, including the cri-du-chat critical region. In children or adults with unexplained mental retardation and normal karyotype results (like this case), an a-CGH should be performed to make an etiological diagnosis, establish the prognosis, order additional medical tests and specific treatments, and offer appropriate genetic counseling.